2008
DOI: 10.1055/s-2008-1039504
|View full text |Cite
|
Sign up to set email alerts
|

Ist eine epidurale Injektionsbehandlung mit hypertoner Kochsalzlösung beim Bandscheibenvorfall sinnvoll? (Die Wirkung von NaCl-Lösung auf Bandscheibengewebe)

Abstract: The effect of sodium chloride solution on disc tissue was investigated in vitro. Tissue material was obtained from 19 discectomies. The specimens were incubated in aqua ad injectionem and in different sodium chloride solutions and weighted regularly during a maximum of 24 hours. Following the incubation periods the specimens were examined histologically. After one hour the surgical specimens showed a weight increase of 290% for aqua bidest., 170% for 0.9% NaCl and 100% for 5.85% NaCl and 10% NaCl. Disc tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[ 3 6 19 30 58 66 67 68 89 95 96 99 118 119 139 140 148 155 158 167 168 181 185 190 191 ] In addition, the efficacy of sodium chloride solution injected into joint spaces or the epidural space has also been described. [ 10 16 17 60 200 ] All the studies demonstrated the efficacy of local anesthetic with steroids; although the disc herniation group showed higher quality with pain relief improvement at 6 and 12 months. One of the major advantages of these trials was that only patients with chronic pain were enrolled and patient homogeneity was observed by recruiting those with similar diagnoses/conditions instead of lumping all diagnostic groups together and/or including those with acute and subacute pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 6 19 30 58 66 67 68 89 95 96 99 118 119 139 140 148 155 158 167 168 181 185 190 191 ] In addition, the efficacy of sodium chloride solution injected into joint spaces or the epidural space has also been described. [ 10 16 17 60 200 ] All the studies demonstrated the efficacy of local anesthetic with steroids; although the disc herniation group showed higher quality with pain relief improvement at 6 and 12 months. One of the major advantages of these trials was that only patients with chronic pain were enrolled and patient homogeneity was observed by recruiting those with similar diagnoses/conditions instead of lumping all diagnostic groups together and/or including those with acute and subacute pain.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of this systematic review may be explained by various mechanisms of steroids and local anesthetics, including the suppression of ectopic discharges from inflamed nerves, enhancing blood flow to ischemic nerve roots, the lysing of iatrogenic and inflammatory adhesions, a washout of proinflammatory cytokines, and reversal of peripheral and central sensitization. [ 10 30 47 58 60 68 77 89 95 96 179 190 198 200 ] Bicket et al . [ 12 ] hypothesized a placebo effect with epidural injections, especially those administered via the transforaminal approach, often with reproduction of radicular symptoms, which is not observed with soft tissue injections, resulting in high levels of placebo effect and undermining the effectiveness of blinding.…”
Section: Discussionmentioning
confidence: 99%